Pengaruh Kedisiplinan Karyawan Terhadap Produktivitas Kerja di PT Glostar Indonesia - Anisa Maharani; Mariati Tirta Wiyata (Winter Journal: IMWI Student Research Journal, 2020)
This study aims to examine the effect of employee discipline on work productivity at PT Glostar Indonesia 1 Cikembar Sukabumi. The research method used is a survey method with a quantitative approach. Data collection methods to obtain primary data in the field using a questionnaire. The quality of the questionnaire data obtained from the respondents was tested to prove its validity and reliability. Furthermore, to test how the influence of employee discipline variables (independent) on work productivity variables (dependent) was carried out using regression analysis test tools. Respondents in this study were 50 employees in the B3 Building (Automation Floor) PT Glostar Indonesia 1 Cikembar Sukabumi. Based on the results of data processing and analysis, the authors found that there was a positive influence between employee discipline and work productivity at PT Glostar Indonesia 1 Cikembar Sukabumi. To be able to increase employee discipline, it is necessary to consider the provision of a comfortable and conducive workspace, not too many rules for employees, and the application of a fair reward and punishment scheme. Meanwhile, to increase work productivity, in addition to building employee discipline, it can also provide a good work environment and provide training or training to employees.